A6.16 Dectin-2 is essentially involved in innate immune response of experimental arthritis. (13th February 2015) - Stögner, V; Shvets, T; Niederreiter, B; Koenders, M; van den Berg, WB; Smolen, JS; Redlich, K; Hayer, S
Abstract : Background: C-type lectin receptors, like Toll-like receptors, belong to the pathogen pattern recognition family (PPR) and are essentially involved in immune responses against microbial infections. Dectin-2 (also known as Clec4n) is mainly expressed on myeloid cells and has been shown to interact with mannan ligands of candida albicans, mycobacteria and house dust mite. The role of Dectin-2 in autoimmune diseases has been less elucidated. Purpose: To investigate the role of Dectin-2 deficiency in the development and severity of experimental arthritis using the K/BxN serum transfer model. Methods: We administered 100 µl serum from K/BxN mice into Dectin-2 -/- and wt (Dectin-2 +/+ ) mice on day 1 and 3. We assessed daily clinical signs of arthritis including increase in paw swelling and loss of grip strength on a scale from 0 to 3 (no to severe swelling) or 0 to -3 (no to severe loss of grip strength), respectively. On day 11 we analysed gait profiles using the CatWalk gait analysis system. One day later, we sacrificed the animals, collected serum for cytokine analysis and isolated hind paws for subsequent histological analysis. We assessed quantitatively the extent of synovial inflammation (on H&E stained sections), number of osteoclasts and subchondral bone erosions (on TRAP stained sections) and cartilage damage (on TB stained sections) with Osteomeasure software. Immunohistochemical stainings were used to identify neutrophil granulocytes (7/4 clone), macrophages (F4/80 clone), T cells (CD3ab) and B cells (CD45R) within inflammatory synovial tissue using TissueQuest software. Results: We found a significant reduction in clinical signs of arthritis such as paw swelling and loss of grip strength as well as a significant prevention of loss of body weight in the K/BxN serum transfer model in Dectin-2 -/- mice compared to wt mice. Furthermore, we found a significant protection from functional impairment shown by increased gait parameters such as maximal intensity and print area in Dectin-2 -/- mice. Lack of Dectin-2 revealed a significant protection from synovial inflammation, generation of synovial bone-resorbing osteoclasts and formation of subchondral bone erosion as quantitatively assessed in hind paw sections. Consistently, we observed a significant protection from proteoglycan loss in articular cartilage in Dectin-2 -/- mice compared to wt mice. We found a significant reduction of infiltrating neutrophil granulocytes into the inflamed joints in mice lacking Dectin-2. Conclusion: C-type lectin receptor Dectin-2 is essentially involved in the regulation of the innate immune response in K/BxN serum transfer model. Lack of Dectin-2 significantly diminished the infiltration of inflammatory cells, particularly of neutrophil granulocytes, responsible in driving inflammatory responses and subsequent structural bone and cartilage damage.